Relationship between Comorbidity of Cluster Personality Disorders with Major Depression Disorder and Depression Relapse - Shima Tamanaei-Far; Parvaneh Mohammadkhani; Abbas Pourshahbaz (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: this research studied the relation between cluster B personality disorders and major depression disorder with relapse. Materials & Methods: In this analytical and comparative study, samples consisted of the major depressive disorders patients that had experienced major depression through 5 years ago and were experiencing partial remission in research time. Samples were selected by non probability sampling in outpatient centers. The patients with more than two relapses were assigned as case group and the patients without any relapse were assigned as control group (two groups on the base of demographic in formations were matched). They completed BDI_II and SCID_II to assess cluster B personality disorders, and a questionnaire made by researcher to gather information's. Results: Comorbidity of borderline personality disorder (P<0.001) and narcissitic personality disorder (P=0.016) with depression in patient with relapse of the depression is more significantly than patients with first episode of depression, but comorbidity of exhibitive personality disorder with depression and relapse had no significant difference between two groups (P=0.401). Conclusion: according to the relationship between narcissistic and borderline personality disorders and the role of them in relapse of depression, for making an effective psychotherapy for depression, it is necessary to consider personality beside special symptoms.